Conductive supramolecular acrylate hydrogels enabled by quaternized chitosan ionic crosslinking for high-fidelity 3D printing - Lukas A. Bauman; Boxin Zhao (Carbohydrate Polymer Technologies and Applications)
While 3D printing has enabled the fabrication of hydrogels with complex structures, high fidelity techniques (vat polymerization) that enable precisely engineered design of hydrogels require stiff structures to withstand the forces of printing. This is a pressing research gap in hydrogel vat-polymerization 3D printing. To address this limitation, a novel ionic crosslinker consisting of quaternized chitosan complexed with 3-sulfopropyl acrylate was used to form supramolecular 2-hydroxyethyl acrylate organogel precursors. The Cyrene organogel enhanced mechanical properties enabling the printing of high-fidelity structures; the final compliant hydrogels were then obtained through solvent exchange with water. This yielded high-fidelity 3D-printed conductive supramolecular hydrogels with tensile properties of 288±29 kPa at 516±37 % elongation and compressive properties of 572±34 kPa at 65±4 % strain with uniform swelling (320–350 %). Nuclear magnetic resonance and conductivity measurements confirmed SPA-rich blocks within the hydrogel network and the solvent-dependent copolymer structure. Furthermore, through varying the anionic acrylate concentration, ultimate strain between 222 % and 516 % was achieved at a constant elastic modulus. Additionally, electrical properties were tunable with conductivity reaching 156 mS/m at 7 MH in ultrapure water. This work advances applications of quaternized chitosan as an ionic crosslinker in printable conductive hydrogels, opening new applications in medical and technological fields.